Nonalcoholic non-virus-related hepatocellular carcinoma arising from nonsteatotic liver: Clinical and pathological features. Issue 5 (4th February 2022) - Shigematsu, Yasuyuki; Kanda, Hiroaki; Amori, Gulanbar; Takahashi, Yu; Takazawa, Yutaka; Inamura, Kentaro
Abstract : Abstract: Nonalcoholic non-virus-related hepatocellular carcinoma (NANV-HCC) is considered to occur in steatotic livers; however, emerging evidence indicates that a subset of NANV-HCC occurs in nonsteatotic livers. Currently, little information is available regarding this subset. This study sought to provide the clinical and pathological features of NANV-HCC in nonsteatotic livers. We retrospectively investigated the clinicopathological features of 101 consecutive patients with NANV-HCC treated with a curative-intent hepatectomy. A background liver with <5% steatosis by area was regarded as a nonsteatotic liver. Survivals of patient subgroups were estimated using the Kaplan–Meier method, and log-rank tests were conducted to assess the survival difference. Multivariate analysis was performed with the Cox proportional hazards method. Overall, 34 of 101 patients with NANV-HCC were found to have a nonsteatotic liver. Vascular invasion of the tumor was more frequently observed in patients with a nonsteatotic liver than in those with a steatotic liver ( P = .03). The extent of lobular inflammation and fibrosis did not differ between patients with and without steatosis in the liver. NANV-HCC with a nonsteatotic liver was independently associated with a shorter disease-free survival (DFS) (hazard ratio [HR] 2.14; 95% confidence interval [CI] 1.21–3.80; P = .009) and a shorter overall survival (OS) (HR 2.79; 95% CI 1.27–6.16; P = .01) than NANV-HCC with a steatotic liver. The absence of steatosis in the liver is independently associated with shorter DFS and OS in patients with NANV-HCC. Our findings indicate that nonsteatotic liver can be a surrogate phenotype of aggressive NANV-HCC. Abstract : Supplemental Digital Content is available in the text